Rh(iii)-Catalyzed directed C–H carbenoid coupling reveals aromatic bisphosphonates inhibiting metallo- and Serine-β-lactamases. Issue 8 (8th February 2018) - Zhang, Chen; Pu, Yan-chi; Yu, Zhu-Jun; Wu, Cheng-yong; Brem, Jürgen; McDonough, Michael A.; Schofield, Christopher J.; Li, Guo-Bo; Wu, Yong
Abstract : The C–H coupling of arenes with diazo-methylene-diphosphonates enables efficient synthesis of new diphosphonates, which exhibit dual MBL and SBL inhibition. Abstract : We report the highly efficient and scalable Rh(iii )-catalyzed C–H coupling of arenes with diazo-methylene-diphosphonates to give structurally diverse aromatic bisphosphonates in good to excellent yields. These bisphosphonates are one of the very few classes of inhibitors acting against the mechanistically distinct metallo-β-lactamases and serine-β-lactamases and thus represent good starting points for the development of broad spectrum β-lactamase inhibitors.